CONTRASTING MEANINGS IN ENGLISH AND UZBEK LINGUOCULTURES: OXYMORONS AND THEIR TRANSLATION CHALLENGES - Muattar Temirova (TADQIQOTLAR, 2025)
Abstract. This article analyzes into the comparative analysis of oxymorons as a stylistic device within English and Uzbek linguocultures. It explores how these paradoxical expressions, which juxtapose contradictory terms, reflect cultural nuances and cognitive frameworks specific to each language. The study highlights the significant challenges translators face when attempting to convey the intended meaning, stylistic effect, and cultural resonance of oxymorons from one language to another. Drawing upon principles of contrastive linguistics, translation theory, and cultural semantics, the article examines various scholarly opinions and provides illustrative examples to demonstrate the complexities involved. It argues that successful translation of oxymorons requires not only linguistic proficiency but also a deep understanding of the source and target linguocultures to navigate the conflicting meanings effectively.